2023
DOI: 10.28991/cej-2023-09-11-017
|View full text |Cite
|
Sign up to set email alerts
|

Solving Innovative Problems of Thrust Vector Control Based on Euler's Scientific Legacy

Yuri A. Sazonov,
Mikhail A. Mokhov,
Inna V. Gryaznova
et al.

Abstract: This study aims to develop an interdisciplinary approach to solving innovative thrust vector control problems. The methodology involves the development of a working hypothesis about the ejection process when using a controlled nozzle to deflect the thrust vector (velocity vector) in any direction within a complete geometric sphere. When developing the working hypothesis, a multilateral analysis of individual facts and scientific and technical information is performed using tools in the "big data" area, assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…𝑄 𝑔.𝑖𝑛 𝑄 𝑔.𝑖𝑛 +𝑄 𝑙.𝑖𝑛 (22) where 𝑄 𝑔.𝑖𝑛is the volume flow rate of gas, reduced to receiving conditions (at the inlet to the gas separator), m 3 /day; 𝑄 𝑙.𝑖𝑛liquid volume flow rate, reduced to receiving conditions (at the inlet to the gas separator), m 3 /day. 2.…”
Section: Results Of Bench Tests Of Centrifugal Gas Separator On Visco...mentioning
confidence: 99%
See 1 more Smart Citation
“…𝑄 𝑔.𝑖𝑛 𝑄 𝑔.𝑖𝑛 +𝑄 𝑙.𝑖𝑛 (22) where 𝑄 𝑔.𝑖𝑛is the volume flow rate of gas, reduced to receiving conditions (at the inlet to the gas separator), m 3 /day; 𝑄 𝑙.𝑖𝑛liquid volume flow rate, reduced to receiving conditions (at the inlet to the gas separator), m 3 /day. 2.…”
Section: Results Of Bench Tests Of Centrifugal Gas Separator On Visco...mentioning
confidence: 99%
“…There are not many scientific works published in the open press, devoted to the analysis of the characteristics of downhole screw pumps on viscous gas-liquid mixtures in a wide range of gas contents. Studies of single screw pumps on viscous liquids have been reported in literature (18,19), and on low-viscosity gas-liquid mixtures also reported (20)(21)(22).…”
Section: Characteristics Of Borehole Screw Pump Operation On Gas-liqu...mentioning
confidence: 99%
“…This problem is so difficult to solve that successful attempts have been made to write hydromechanical equations of motion in such a way that they do not contain the explicit presence of pressure as an unknown quantity [17][18][19]. The method for removing pressure in explicit notation from the equations of hydrodynamics is the method of transitioning to "non-primitive" variables.…”
Section: -Introductionmentioning
confidence: 99%
“…However, when solving hydrodynamic problems, it does not have to be determined at each iterative step of the calculation. The pressure can be determined separately from the equation written specifically for pressure determination [18,19]. The essence of the method of transition to "non-primitive" variables is as follows: each term of the equation of motion of a continuous medium is a vector, and accordingly, the "vortex" operation can be applied to each term of the equation of motion [18][19][20].…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation